Scale of concern about infection with a variant of COVID-19 (EPCNVCov-19) - Renzo Felipe Carranza-Esteban; Oscar Javier Mamani-Benito; Percy G. Ruiz-Mamani; Christian R. Mejia (Revista Cubana de Medicina Militar)
Introduction: Since the beginning of the COVID-19 pandemic, several variants of the virus have been documented, generating greater concern among the population. Objective: To analyze the psychometric properties of a scale of concern about the contagion of a variant of COVID-19 (EPCNVCov-19). Methods: An instrumental study, which adapted 5 Likert-type questions from a previously validated scale (EPCNVCov-19), was conducted and applied virtually to 407 people (56.5 % women) from different departments in Peru. To analyze the evidence of content validity, the Aiken V coefficient was used, the analysis of internal structure through confirmatory factor analysis, and reliability was estimated by means of the Omega coefficient. In addition, analyses of invariance by gender and convergent and discriminant validity were performed. Results: The EPCNVCov-19 was adapted in time and context, and the items received a satisfactory rating from the experts (Aiken's V coefficient > 0.70). With the goodness-of-fit indices, the unidimensional structure of the scale was confirmed (χ2 = 9,36, df = 5, p = 0,09; CFI = 0,999; TLI = 0.999; RMSEA = 0.046 [CI90 % 0.00 - 0.092] and SRMR = 0.015). The invariance analysis shows that the EPCNVCov-19 can be used in individuals of both sexes. Conclusion: The scale presents acceptable reliability (ω > 0,8). Likewise, evidence of convergent and discriminant validity was achieved. In conclusion, the EPCNVCov-19 is a valid, reliable and sex-invariant brief measure in the Peruvian population.